2012
DOI: 10.1371/journal.pone.0030663
|View full text |Cite
|
Sign up to set email alerts
|

Grasp It Loudly! Supporting Actions with Semantically Congruent Spoken Action Words

Abstract: Evidence for cross-talk between motor and language brain structures has accumulated over the past several years. However, while a significant amount of research has focused on the interaction between language perception and action, little attention has been paid to the potential impact of language production on overt motor behaviour.The aim of the present study was to test whether verbalizing during a grasp-to-displace action would affect motor behaviour and, if so, whether this effect would depend on the sema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 55 publications
(65 reference statements)
6
17
0
Order By: Relevance
“…Increased grip force was recorded approximately 260 ms after hearing action-related verbs but not after hearing non-action nouns. Similar effects of word type on arm movement have been observed in several other kinematic studies (Boulenger et al , 2006; Fargier et al , 2012; Aravena et al, 2012). These results indicate that the link between language and motor control is sensitive to subtle manipulations of linguistic context.…”
Section: Introductionsupporting
confidence: 86%
“…Increased grip force was recorded approximately 260 ms after hearing action-related verbs but not after hearing non-action nouns. Similar effects of word type on arm movement have been observed in several other kinematic studies (Boulenger et al , 2006; Fargier et al , 2012; Aravena et al, 2012). These results indicate that the link between language and motor control is sensitive to subtle manipulations of linguistic context.…”
Section: Introductionsupporting
confidence: 86%
“…These effects are in accordance with other studies that have investigated the activation of motor areas during language processing. Indeed, it has been shown that not only observing actions but also perceiving or pronouncing action words can activate the motor system (Tettamanti et al, 2005; Aziz-Zadeh and Damasio, 2008; Boulenger et al, 2009; Pulvermüller and Fadiga, 2010; Fargier et al, 2012). Aravena et al (2010), for instance, studied whether the compatibility of a performed hand action and an action described in a sentence would influence brain motor potentials.…”
Section: Discussionmentioning
confidence: 99%
“…[8], reading [5], naming [12], verbal fluency [6] and verbal memory tasks [7]. Similarly, the complexity of the motor task highly various between the experiments including only one [6] or both hands [7].…”
Section: Dependenciesmentioning
confidence: 99%
“…Similarly, the complexity of the motor task highly various between the experiments including only one [6] or both hands [7]. Furthermore, the task and stimuli language, the experimental setup as well as the used software differs between the experiments [4][5][6][7][8], [12]. Open Source software allows researchers to reproduce results, as well as to modify only one or a few aspects of an experimental setting to produce comparable results.…”
Section: Dependenciesmentioning
confidence: 99%